Vertical profiles and temporal variations of greenhouse gases in the stratosphere over Syowa Station, Antarctica - Daisuke, Goto; Shinji, Morimoto; Shuji, Aoki; Satoshi, Sugawara; Shigeyuki, Ishidoya; Yoichi, Inai; Sakae, Toyoda; Hideyuki, Honda; Gen, Hashida; Takashi, Yamanouchi; Takakiyo, Nakazawa (2017)
第8回極域科学シンポジウム/個別セッション：[OM] 極域気水圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OM] Polar Meteorology and Glaciology Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object